Stabilitas Tanah Plastisitas Rendah Dengan Semen - s, Pirmadona; Muhardi, Muhardi; Kurniawandy, Alex (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Soil is a material that serves as an support for the basis of a constuction, be it construction of buildings, bridges and roads. Each region has different soil characteristics in other regions, there have bearing capacity is good and some are bad. To overcome this, it is necessary to repair soil with stabilization method. One way of soil stabilization is with cement. In this study, the cement used are OPC cement and PCC cement. This study focuses on the effect of OPC cement content and PCC against the value of CBR and free compressive strength (UCS) of land. Soil samples tested in this study is the low plasticity clay derived from the intersection Inpress km.11 Perawang, Siak. Content variation mixture used is 5%, 10%, 15%, 20% on each of the OPC cement and PCC to do the same curing time for 14 days.The results showed that the increasing levels of mixed cement both OPC cement and cement PCC, then the value of CBR and UCS will be even greater. The maximum increase of UCS value in the soil mix with 20% OPC and 20% PCC, where the value of each are 6.2 MPa and 2.6 MPa. At levels of 10% OPC and 10% PCC, CBR value of each is 369.6% and 189.8%. This indicates that the OPC cement and PCC cement can improve the physical and mechanical properties of clay low plasticity.Keywords: Low plasticity clay, CBR, UCS, OPC, PCC